Wireless networks from the physical layer to communication, computing, sensing, and control - Franceschetti, Giorgio; Stornelli, Sabatino (Amsterdam ; Boston : Elsevier Academic Press, 2006)
Awarded by the International Calabria's Prize! This multidisciplinary volume originates from lectures presented at a short course on wireless communications in Capri, Italy. This globally attended conference has produced an exceptional book written by pioneers in the field. Lecturers at Capri included pillars in the fields of electromagnetics, communications, information technology and mathematics. As communications technology becomes increasingly wireless, an interdisciplinary viewpoint is necessary for professionals to correct problems and avoid others before they occur. Wireless Networks covers critical technology within WLAN, ad hoc networks, data distribution, TV, radio, and personal mobile devices. As networks become wireless, engineers face increased difficulty securing its malleable boundaries. This book discusses security solutions such as sensor technology that prevent unwanted intrusion. Connectivity is also addressed, featuring chapters on antennas, bandwidth and frequencies. Editors Franceschetti and Stornelli have done a great service to the wireless communications community in creating a compendium that delivers this spectrum of essential information in one reference. *Presents a uniquely panoramic view of wireless networks with viewpoints from engineering, computing, and mathematics *The technology is discussed in theory as well as in practice to help engineers design and modify networks *Globally recognized experts share their critical insight on sensor technology, transfering protocol, ad-hoc networks, and more.
Wireless networks and their context -- The wireless communications physical layer -- Handset communication antennas including human interactions -- Wireless channel model -- Ad hoc wireless networks -- Sensor networks -- Wireless networks and the possible next revolution in information technology.
Lectures presented in Capri, Italy, fall of 2004.
Includes bibliographical references and index.
Keywords: Wireless LANs -- Congresses; Personal communication service systems -- Congresses; Electronic books